PENGARUH VOLUME KARGO IMPOR TERHADAP TINGKAT IRREGULARITY BARANG IMPOR - ANDRI PRIMADI; ILZA ILZA (Institut Transportasi dan Logistik Trisakti, 2015)
This study is aimed to find out how much influence the import cargo of PT Indonesia Air Asia to the import goods irregularity. The researchers used 2 data collective methods which are field research and library research. Then, the data is analyzed using linearity regression, coefficient correlation, determinant coefficient and hypothesis test. The result showed that there is a low relation between import cargo volume and irregularity based on linearity regression; Y = 5.220 + 0.001 X. Coefficient correlation analysis r = 0.01 means that there is no correlation between X and Y. The determinant coefficient in 1 % showed that the contribution of cargo volume to the irregularity is 1 % while 99 % is the other factors. The last result is hypothesis test which showed t count < t table (0.031 < 1.812). It means that Ho is accepted and of course Ha is rejected. The conclusion of the results is that there is a low and negative relation between import cargo volume and the irregularity goods of PT Indonesia Air Asia.